Figurative language processing in atypical populations: the ASD perspective - Vulchanova, Mila; Saldaña, David; Chahboun, Sobh; Vulchanov, Valentin (Frontiers in Human Neuroscience, 2015)
This paper is intended to provide a critical overview of experimental and clinical research documenting problems in figurative language processing in atypical populations with a focus on the Autistic Spectrum. Research in the comprehension and processing of figurative language in autism invariably documents problems in this area. The greater paradox is that even at the higher end of the spectrum or in the cases of linguistically talented individuals with Asperger syndrome, where structural language competence is intact, problems with extended language persist. If we assume that figurative and extended uses of language essentially depend on the perception and processing of more concrete core concepts and phenomena, the commonly observed failure in atypical populations to understand figurative language remains a puzzle. Various accounts have been offered to explain this issue, ranging from linking potential failure directly to overall structural language competence (Brock et al., 2008; Norbury, 2005) to right-hemispheric involvement (Gold and Faust, 2010). We argue that the dissociation between structural language and figurative language competence in autism should be sought in more general cognitive mechanisms and traits in the autistic phenotype (e.g., in terms of weak central coherence, Vulchanova et al., 2012b), as well as failure at on-line semantic integration with increased complexity and diversity of the stimuli (Coulson and van Petten, 2002). This perspective is even more compelling in light of similar problems in a number of conditions, including both acquired (e.g., Aphasia) and developmental disorders (Williams Syndrome). This dissociation argues against a simple continuity view of language interpretation.